Textile Wastewater Treatment Through Plant–Microbe Synergism in a Floating Treatment Wetland System. Issue 4 (July 2022) - Tusief, Qamar; Mohsin, Muhammad; Hussan Malik, Mumtaz; Asghar, Hafiz Naeem; Sardar, Shaheen
Textile wastewater treatment is a complex process that requires a range of chemicals and generates hazardous sludge. This article evaluates a chemical-free, floating treatment wetlands system for the treatment of textile wastewater containing reactive red and reactive yellow dyes. Two aquatic plants, Eichhornia crassipes Solms and Pistia stratiotes L., were selected and vegetated in the system. The efficacy of the system was enhanced by inoculation of two pollutant-degrading and plant growth-promoting bacteria: Bacillus cereus and Bacillus subtilis . The eight treatments were designed with different combinations of plants and bacteria. The performance of the system was evaluated through key parameters of electrical conductivity, total dissolved solid, total suspended solids, biological oxygen demand, chemical oxygen demand, and dye concentration for the treated wastewater. The best treatment achieved the optimized plant–bacteria synergism and exhibited good reductions in the physicochemical parameters and the values of all the wastewater parameters were within the limits set in the standards of National Environmental Quality Standards and Zero Discharge of Hazardous Chemicals Program.